Local orbital degeneracy lifting as a precursor to an orbital-selective Peierls transition - E. S. Bozin (Nature Portfolio, 2019)
A common feature of many transition metal materials is global symmetry breaking at low temperatures. Here the authors show that such materials are characterized by fluctuating symmetry-lowering distortions that exist pre-formed in higher temperature phases with greater average symmetry.